História e tradição - Souza, Viviane Raquel Denadai [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This work aims at uniting the historical reality of the city with a tradition of Jaú giving current policy basis for the development of the work of restoration and revitalization of the Square Oswaldo Galvão de France (Jau Square Bus Station), Tancredo Neves Square and Old Warehouse Coffee, located in central city, in a situation of abandonment by the government, intended to be restricted to cultural events and art in all its aspects in order to meet the needs of the population

Este trabalho visa unir a realidade histórica da cidade de Jaú com uma tradição atual dando base de orientação para o desenvolvimento do trabalho de revitalização e restauro da Praça Oswaldo Galvão de França (Praça da Rodoviária de Jaú), da Praça Tancredo Neves e do antigo Armazém de Café, localizados na região central da cidade, em situação de abandono pelo poder público, cuja intenção se restringirá à realização de eventos culturais e artístico em todas as suas vertentes, a fim de atender às necessidades da população
Keywords: Café - História - Jau (SP); Grupos de rock - Jau (SP); Arquitetura - Conservação e restauração; Jau (SP) - Praças